KOORDINASI MAKNA PESAN PASANGAN SUAMI-ISTRI YANG MENJALANKAN HUBUNGAN PERNIKAHAN JARAK JAUH (Studi Fenomenologi pada Pasangan yang Menjalankan Hubungan Pernikahan Jarak Jauh di Desa Cianten) - Fatma Nurfaidah (2022)
Coordinate the meaning of messages in convertation is very important to do. Often times, coordinating with other people is considered easy, but in reality it is very difficult to do. Someone who carries different message meanings in a conversation can cause other people to respond differently based on managing their own meaning. This study aims to find out how marriage couples who run long-distance marriages in Cianten Village coordinate the meaning in their conversations using the theory of coordinated meaning management. This research used qualitative approach with phenomenological methods and the use of primary and secondary data sources. The sampling technique was carried out by purposive sampling. Research used four stages of data analysis according to Moustakas. The results of this study were found ways to coordinate the meaning of messages carried out by couples who run long distance relationships, namely by using language that is easily understood by both partners, paying attention to intonation and articulation when comminucating, using gestures, facial expressions and adding stickers also emoticons in their chats. Along with that, in addition paying attention to the content of the message that is being conveyed by the partner, thinking about the reaction or action to be taken, requesting the message that is not understood and resumming the message being discussed at the end of the conversation is done by husband and wife to create the meaning of the same message.